2017
DOI: 10.1189/jlb.3ma0117-037r
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling reveals functional dichotomy between human slan+ non-classical monocytes and myeloid dendritic cells

Abstract: Human 6-sulfo LacNac-positive (slan) cells have been subject to a paradigm debate. They have previously been classified as a distinct dendritic cell (DC) subset. However, evidence has emerged that they may be more related to monocytes than to DCs. To gain deeper insight into the functional specialization of slan cells, we have compared them with both conventional myeloid DC subsets (CD1c and CD141) in human peripheral blood (PB). With the use of genome-wide transcriptional profiling, as well as functional test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 47 publications
(84 reference statements)
7
37
0
Order By: Relevance
“…Concerning the question of whether SLAN + cells are monocytes or DC, their gene expression is clearly monocytic. 13,[198][199][200] Furthermore, recent human in vivo and xenograft experiments support the hypothesis that non-classical monocytes differentiate from classical monocytes by down-regulating inflammatory pathways and adopting a CX3CR + CCR2 -CD11c hi CD11b lo phenotype. 201 However, it should be noted that gene expression alone does not absolutely exclude an independent origin of SLAN + cells from the remainder of CD16 + monocytes and that SLAN itself was not measured on the output of cells derived from human classical monocytes in the adoptive transfer experiments.…”
Section: Cd16 + Non-classical Monocytes Slan + DC and Dc4mentioning
confidence: 71%
See 1 more Smart Citation
“…Concerning the question of whether SLAN + cells are monocytes or DC, their gene expression is clearly monocytic. 13,[198][199][200] Furthermore, recent human in vivo and xenograft experiments support the hypothesis that non-classical monocytes differentiate from classical monocytes by down-regulating inflammatory pathways and adopting a CX3CR + CCR2 -CD11c hi CD11b lo phenotype. 201 However, it should be noted that gene expression alone does not absolutely exclude an independent origin of SLAN + cells from the remainder of CD16 + monocytes and that SLAN itself was not measured on the output of cells derived from human classical monocytes in the adoptive transfer experiments.…”
Section: Cd16 + Non-classical Monocytes Slan + DC and Dc4mentioning
confidence: 71%
“…The simple facts are that CD16 + monocytes are heterogeneous and that SLAN expression identifies a subpopulation with lower CD11b, CD14 and CD36 but higher expression of CD16. Concerning the question of whether SLAN + cells are monocytes or DC, their gene expression is clearly monocytic . Furthermore, recent human in vivo and xenograft experiments support the hypothesis that non‐classical monocytes differentiate from classical monocytes by down‐regulating inflammatory pathways and adopting a CX3CR + CCR2 – CD11c hi CD11b lo phenotype .…”
Section: Cd16+ Non‐classical Monocytes Slan+ DC and Dc4mentioning
confidence: 92%
“…DCs, monocytes, and macrophages are now classified based on their identified precursor cell. For slan + cells, transcriptomic studies collectively demonstrated a gene signature shared with monocytes rather than bona fide DCs (18). We therefore propose calling these cells slanMo instead of slanDCs, as already recommended by others (19).…”
Section: Introductionmentioning
confidence: 76%
“…Several other hematopoietic cell subsets, involved in the dysplastic clone and/or in the immunopathogenesis of MDS, have been described, including aberrancies in mast cells, changes of frequency in plasmacytoid dendritic cells, myeloid dendritic cells (mDC1 and mDC2), myeloid-derived suppressor cells (MDSC) and T cell subsets [24,25]. Increased frequencies of MDSCs and T-regulatory cells are thought to reflect an immunosuppressive environment in high risk MDS [2,26].…”
Section: Additional Cell-subsets Of Interestmentioning
confidence: 99%